Lone Inventors as Sources of Breakthroughs: Myth or Reality? - Singh, Jasjit; Fleming, Lee (Management Science, 2010)
Are lone inventors more or less likely to invent breakthroughs? Recent research has attempted to resolve this question by considering the variance of creative outcome distributions. It has implicitly assumed a symmetric thickening or thinning of both tails, i.e., that a greater probability of breakthroughs comes at the cost of a greater probability of failures. In contrast, we propose that collaboration can have opposite effects at the two extremes: it reduces the probability of very poor outcomes—because of more rigorous selection processes—while simultaneously increasing the probability of extremely successful outcomes—because of greater recombinant opportunity in creative search. Analysis of over half a million patented inventions supports these arguments: Individuals working alone, especially those without affiliation to organizations, are less likely to achieve breakthroughs and more likely to invent particularly poor outcomes. Quantile regressions demonstrate that the effect is more than an upward mean shift. We find partial mediation of the effect of collaboration on extreme outcomes by the diversity of technical experience of team members and by the size of team members' external collaboration networks. Supporting our meta-argument for the importance of examining each tail of the distribution separately, experience diversity helps trim poor outcomes significantly more than it helps create breakthroughs, relative to the effect of external networks.